2022
DOI: 10.26434/chemrxiv-2022-cfrfk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heparan Sulfate Glycomimetics via Iterative Assembly of “Clickable” Disaccharides

Abstract: Heparan sulfate (HS) glycosaminoglycans are widely expressed on the mammalian cell surfaces and extracellular matrices and play important roles in variety of cell functions. Studies on the structure-activity relationships of HS have long been hampered by the challenges in obtaining chemically defined HS structures with unique sulfation patterns. Here, we report a new approach to HS glycomimetics based on iterative assembly of clickable disaccharide building blocks that mimic the disaccharide repeating units of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It should be pointed out that in parallel to our work, Niu and coworkers recently submitted the synthesis of head to tail HS mimetics through the alkyne azide [3+2] cycloaddition reaction. [40] Sulfated monosaccharide serine conjugate has been utilized to form glyco-amino acid oligomers to mimic HS with only homo-oligomers prepared without varying sulfation patterns within the molecule. [41] These reports combined with our work suggest linear HS mimetics strategies provide an exciting approach to expedite the synthesis of HS-like compounds and faciliate the understanding of the fascinating biological functions of HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that in parallel to our work, Niu and coworkers recently submitted the synthesis of head to tail HS mimetics through the alkyne azide [3+2] cycloaddition reaction. [40] Sulfated monosaccharide serine conjugate has been utilized to form glyco-amino acid oligomers to mimic HS with only homo-oligomers prepared without varying sulfation patterns within the molecule. [41] These reports combined with our work suggest linear HS mimetics strategies provide an exciting approach to expedite the synthesis of HS-like compounds and faciliate the understanding of the fascinating biological functions of HS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our study, other "head-to-tail" HS mimetics have also been reported (Section S2). [42,43] Thus, reducing the complexity of synthesis through the "head-to-tail" linear mimetics formation represents a new direction to expedite the preparation of HS mimics and facilitate the understanding of their exciting biological functions. 33, 33 a-z) on FGF-2 interaction with heparin through a competition SPR assay.…”
Section: Discussionmentioning
confidence: 99%